The State As Rights-Facilitator: Reconciling Branches of Privacy Doctrine Through Consent - Kobriger, Kate (Columbia Journal of Gender and Law, 2023)
The State As Rights-Facilitator: Reconciling Branches of Privacy Doctrine Through Consent